Child mortality in the state of Bahia: conditioners and spatial analysis (Research, Society and Development, 2020)
Infant mortality is still a problem that afflicts, above all, the most neglected populations in Brazil. Despite efforts to reduce it, the northern and northeastern states have the highest rates in the national scenario. The present study aims to analyze the incidence rates of infant mortality in the state of Bahia in the spatial context and its determinants. The methodology used for the development of this study incorporated spatial and econometric analyzes, using secondary data from the Brazilian Demographic Census of 2010, from the Brazilian Institute of Geography and Statistics. From then on, thematic maps were elaborated, using geoprocessing tools. This followed with the identification and representation of the spatial distribution of infant mortality, as well as its correspondence with other socioeconomic indicators, such as the illiteracy rate, the rate of children vulnerable to poverty, inadequate sanitation and inadequate garbage collection. Data disparities between municipalities in the semi-arid region of Bahia and other regions were also analyzed. The results allowed to identify that the semi-arid region of the State is the one that presents the worst results for all the studied variables, what allows to affirm that it is the region most in need of public policies.